The Effect of Empowering Leadership on Employee Engagement, Knowledge Sharing, and Innovative Behavior of Private Banking Hrd Employees in Indonesia - Ica Raditia; Lia Amalia (Journal of Social Research, 2025)
Management strategies and leadership models can influence employee performance and productivity. Competent human resources are crucial assets for the stability and growth of the banking sector. HRD employees play a vital role in managing human resources in the banking industry. Research on HRD employees is necessary to analyze the impact of management strategies on performance and productivity. Empowering leadership is one leadership model believed to enhance employee engagement, knowledge sharing, and innovative behavior. The primary objective of this study is to examine the role of empowering leadership in increasing these behaviors. The study's respondents consisted of 175 HRD employees from private banking industries in Indonesia. The data were processed using Structural Equation Modeling (SEM). Several findings from this study indicate that empowering leadership positively influences employee engagement and innovative behavior. Additionally, knowledge sharing has a positive effect on innovative behavior. However, empowering leadership does not have a direct positive impact on knowledge sharing unless mediated by employee engagement. Moreover, empowering leadership positively affects innovative behavior when mediated through two sequential mediators: employee engagement and knowledge sharing. The managerial implications of this study suggest that implementing an empowering leadership model can foster recognition, emotional support, and career development, thereby enhancing employee engagement. This, in turn, motivates employees to share experiences and information, which can support their creativity.